Lead-lag relationship between stock futures index and cash price index in Malaysia / Ahmad Syazwan Hirun Azaman - Hirun Azaman, Ahmad Syazwan (Faculty of Business Management, Universiti Teknologi MARA, 2018)
The relationship between spot price index and futures price index has been heavily studied by researchers empirically and theoretically. The downside of these studies is that only several studies were conducted in emerging markets and most of them were focused more on the developing market. In perfect markets, relationship between spot index and futures index price changes should be perfect. However, one of these markets may reflect information faster compared to the other market due to market imperfections. This study actually aims to determine the cointegration and causality relationship between stock futures index and cash price index in Malaysia. The data involved in this study includes FTSE Bursa Malaysia Kuala Lumpur Composite Index (KLCI), FTSE Bursa Malaysia KLCI Futures (FKLI) and FTSE Bursa Malaysia KLCI Futures for next month (FKLINM). In this study, several tests like Granger causality test and cointegration test were used in order to study the relationship between the spot price index and frtures price index. The direction of causality relationship of these two variables is unidirectional which runs from cash market to futures market. It shows that the cash market is more active than the futures market.